Myeloperoxidase (MPO) – possible diagnosis biomarker and risk stratification in myocardial inotropism deficit induced by chronic ischemic heart disease - Gabi Valeriu Dinca; Adriana Diaconu; Bogdan-Ioan Coculescu; Gheorghe Manole; Horatiu Vultur; Elena Claudia Coculescu (Romanian Journal of Medical Practice, 2022)
The myeloperoxidase levels of 208 patients with ischemic heart disease hospitalized for congestive heart failure were tested at admission, and discharge after 14 days. The calculations for the serum average concentration/lot/date, were made, subsequent, using the values of the tested parameters regarding MPO (admission and discharge) the mean concentration/lot was made, regardless of time of determination. The calculated average values analyses of the three MPO serum parameters were constantly elevated and permanently matched the myocardial contractility deficiency class. The integrated data of the study, allows us to propose the MPO’s circulating concentration as a diagnosis and risk assessment biomarker in the etiology of myocardial ischemia for chronic cardiac failure.